Power Management System for a Libyan Distribution Network to Meet Future Demand (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Abstract— The continuation of increasing the power demand inLibya leads to raise the voltage regulation issues especially indistribution networks. This requires integrating more distributedgenerators (DGs) into distribution networks to meet suchdemand. However, operating several DGs into distributionnetworks raises stability, power management and voltageregulation challenges in Libyan power systems. This is due to theconfliction of operation between the new integrated DGs and theexisting equipments such as On Load Tap Changes Transformers(OLTCT). This paper introduces a potential solution to operateadditional DG with existing OLTCT using Power ManagementSystem (PMS) supervision to overcome such challenges. ThePMS controller works to supervise controllers of existing OLTCTand controllers of Automatic voltage regulator (AVR) andGovernor (GOV) for additional DG to avoid the voltageregulation issue and to meet future demand.